CO2 adsorbent based on Fe-based aluminum phosphate and preparation method thereof
By introducing Fe into aluminum phosphate and fine regulation, combined with roasting and pyrolysis activation technology, an efficient CO2 adsorbent was developed, solving the limitations of existing adsorbents in adsorption capacity, kinetics and stability, achieving more efficient CO2 capture and lower regeneration energy consumption.
Patent Information
- Application Number
- CN202510076276.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing CO2 adsorbents have limitations in adsorption capacity, adsorption kinetics, thermal stability and chemical stability, and are difficult to meet the needs of industrial-scale CO2 capture.
The CO2 adsorbent based on Fe-based aluminum phosphate is used to improve the adsorption capacity and kinetic properties of the adsorbent through precise metal doping technology and crystal morphology control, and its thermal stability and chemical stability are improved through calcination and pyrolysis activation methods.
The CO2 adsorption capacity of the adsorbent is significantly improved, the adsorption kinetics is optimized, the stability at high temperature is ensured, and the regeneration energy consumption of the adsorbent is reduced, thereby improving the overall operating efficiency.
Smart Images

Figure CN119869432A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide capture, and in particular to a CO2 adsorbent based on Fe-based aluminum phosphate and a preparation method thereof. Background Art
[0002] With the acceleration of global industrialization, carbon dioxide (CO2) emissions continue to increase, leading to an intensified greenhouse effect. In order to mitigate climate change, CO2 capture, utilization and storage (CCUS) technology has become a key means to reduce the content of greenhouse gases in the atmosphere. In CCUS technology, CO2 adsorption technology has attracted much attention due to its high efficiency and operability. Traditional CO2 adsorption materials include physical adsorbents (such as porous carbon, zeolites and metal-organic frameworks) and chemical adsorbents (such as functionalized materials containing amine groups). However, these materials have a series of problems in practical applications, such as limited adsorption capacity, low selectivity, slow kinetics, and decreased performance in humid environments.
[0003] Aluminophosphate is considered to be a potential CO2 adsorption material due to its unique one-dimensional parallel microporous structure and neutral surface properties. 3+ and P 5+ The material is only slightly hydrophilic due to its charge-neutral framework structure connected by oxygen atoms. This structural feature gives ALPO a potential advantage in CO2 adsorption, especially in the process of rapid pressure swing adsorption (PSA), where the stability and life of the adsorption / desorption cycle are long.
[0004] Nevertheless, the preparation and activation methods of ALPO in the prior art still have some limitations, such as the complex preparation process of the adsorbent, high cost, unstable adsorption performance, etc. Therefore, it is necessary to develop a new high-efficiency CO2 adsorbent based on aluminum phosphate modification and a preparation and activation method thereof to solve the problems existing in the prior art and improve the efficiency and economy of CO2 capture. Based on this demand, the present invention provides a new high-efficiency CO2 adsorbent based on aluminum phosphate modification and a preparation and activation method thereof, aiming to provide a CO2 adsorbent with high adsorption capacity, fast adsorption kinetics, good thermal stability and chemical stability to meet the needs of industrial-scale CO2 capture. Summary of the invention
[0005] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a CO2 adsorbent based on Fe-based aluminum phosphate and a preparation method thereof, so as to solve the limitations of the CO2 adsorbent in adsorption capacity, adsorption kinetics, thermal stability and chemical stability proposed in the above background technology.
[0006] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0007] The present invention provides a method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate, the preparation method comprising the following steps:
[0008] 1) mixing aluminum isopropoxide with water, dissolving under stirring, and then sequentially adding orthophosphoric acid and a structure directing agent to form a reaction gel;
[0009] 2) Adding Fe precursor solution and additional water to the reaction gel obtained in step 1) to form a doping system; wherein the aluminum isopropoxide is converted into Al2O3 based on the molar number of aluminum atoms, and the molar ratio of the additional water to Al2O3 is 100-250:1.
[0010] 3) subjecting the doping system obtained in step 2) to a hydrothermal reaction in a reactor to obtain Fe-doped ALPO crystals;
[0011] 4) Further activating the Fe-doped ALPO crystals obtained in step 3) to obtain a CO2 adsorbent based on Fe-based aluminum phosphate.
[0012] The present invention also provides a CO2 adsorbent based on Fe-based aluminum phosphate, which is prepared by the preparation method of the CO2 adsorbent based on Fe-based aluminum phosphate as described above in the present invention.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] 1. Significant improvement in adsorption capacity: Through precise metal doping technology and crystal morphology control, the present invention enables the adsorbent to exhibit a CO2 adsorption capacity that exceeds that of traditional AlPO at all test pressures. This improvement not only expands the application range of the adsorbent, but also provides a more efficient solution for industrial-scale CO2 capture.
[0015] 2. Optimization of adsorption kinetics: The adsorbent of the present invention follows a pseudo first-order model for CO2 adsorption, which means that the adsorption process is not only fast but also easy to control. The optimized kinetic performance enables the adsorbent to reach adsorption equilibrium faster, improving the efficiency of the adsorption process.
[0016] 3. Excellent thermal and chemical stability: The adsorbent of the present invention can remain stable even under high temperature conditions, which makes it very suitable for industrial applications, especially those occasions that require operation in high temperature environments.
[0017] 4. The adsorbent of the present invention has an adsorption heat of no more than 25 kJ / mol. This low adsorption heat characteristic is conducive to the desorption of CO2 by rapid pressure swing adsorption (PSA) without the need for an additional thermal regeneration step. This advantage not only reduces energy consumption, but also simplifies the regeneration process of the adsorbent and improves the overall operating efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the SEM image of 5Fe-AlPO under the condition of water / Al2O3 molar ratio of 400:1 in Comparative Example 1.
[0019] Figure 2 This is the SEM image of 5Fe-AlPO under the condition of water / Al2O3 molar ratio of 100:1 in Example 1. DETAILED DESCRIPTION
[0020] Hereinafter, the Fe-based aluminum phosphate CO2 adsorbent and the preparation method thereof of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0021] [Preparation method of CO2 adsorbent based on Fe-based aluminum phosphate]
[0022] The present invention provides a method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate, the preparation method comprising the following steps:
[0023] 1) mixing aluminum isopropoxide with water, dissolving under stirring, and then sequentially adding orthophosphoric acid and a structure directing agent to form a reaction gel;
[0024] 2) adding an Fe precursor solution and additional water to the reaction gel obtained in step 1) to form a doping system;
[0025] 3) subjecting the doping system obtained in step 2) to a hydrothermal reaction in a reactor to obtain Fe-doped ALPO crystals;
[0026] 4) Further activating the Fe-doped ALPO crystals obtained in step 3) to obtain a CO2 adsorbent based on Fe-based aluminum phosphate.
[0027] In the preparation method provided by the present invention, step 1) is to mix aluminum isopropoxide with water, dissolve under stirring, and then add orthophosphoric acid and a structure directing agent in sequence to form a reaction gel. Specifically:
[0028] The basic reaction of the hydrolysis of aluminum isopropoxide can be expressed as: 2Al(OiPr3)+6H2O→Al2O3+6OiPrH.
[0029] In step 1) of the present invention, aluminum isopropoxide is mixed with water and stirred for 2 to 4.5 hours, which may be 2 to 3 hours or 3 to 4.5 hours. The stirring time is to ensure complete dissolution.
[0030] In step 1) of the present invention, the structure directing agent is one or more of triethylamine, tetraethylammonium hydroxide and cyclohexylamine.
[0031] In step 1) of the present invention, the molar ratio of aluminum isopropoxide, orthophosphoric acid, and structure directing agent is 1: 0.7-1.1: 0.6-1.0. Optionally, the molar ratio of aluminum isopropoxide, orthophosphoric acid, and structure directing agent is 1: 0.7-0.802: 0.6-1.0, 1: 0.802-1.1: 0.6-1.0, 1: 0.7-1.1: 0.6-0.74, 1: 0.7-1.1: 0.74-1.0.
[0032] In step 1) of the present invention, the orthophosphoric acid and the structure directing agent are added dropwise.
[0033] In step 1) of the present invention, the orthophosphoric acid is added and stirred for 0.75 to 1.75 hours, which may be 0.75 to 1 hour or 1 to 1.75 hours. For example, orthophosphoric acid is added dropwise and stirred continuously to form a uniform reaction solution.
[0034] In step 1) of the present invention, the structure directing agent is added and stirred for 18 to 30 hours, which may be 18 to 24 hours or 24 to 30 hours.
[0035] In step 1) of the present invention, the pH value of the reaction gel is 5 to 6.
[0036] In one embodiment, triethylamine (TEA) as a structure directing agent is added dropwise and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0037] In the preparation method provided by the present invention, step 2) is to add Fe precursor solution and supplementary water to the reaction gel obtained in step 1) to form a doping system.
[0038] In step 2) of the present invention, the aluminum isopropoxide is converted to Al2O3 based on the molar number of aluminum atoms, and the molar ratio of water to Al2O3 is 100-250:1, which can be selected as 100-150:1, 150-250:1, etc. Within the aforementioned range, fine regulation of the crystal morphology of the CO2 adsorbent based on Fe-based aluminum phosphate is achieved. The crystal morphology of the CO2 adsorbent based on Fe-based aluminum phosphate is spherical aggregates, which optimizes the pore structure of the adsorbent. If the above range is exceeded, for example, when the molar ratio of water to Al2O3 is 400:1, a columnar single crystal is obtained. The AlPO crystal morphology and pore characteristics obtained under different synthesis conditions were analyzed in detail by SEM and nitrogen adsorption-desorption isotherm tests. The results showed that low water content (such as 400:1 water / Al2O3 molar ratio) led to the formation of columnar crystals, while high water content (such as 100:1 water / Al2O3 molar ratio) formed spherical aggregates, the latter of which exhibited higher CO2 adsorption capacity.
[0039] In step 2) of the present invention, the aluminum isopropoxide is converted to Al2O3 based on the molar number of aluminum atoms, the Fe precursor solution is converted to Fe based on the molar number of iron atoms, and the molar ratio of Fe to Al2O3 is 4:100 to 6.5:100. It can be selected as 4:100 to 5:100 or 5:100 to 6.5:100. Within the above range, the Fe metal precursor is doped into ALPO to optimize its lattice parameters and pore structure and improve the adsorption performance of CO2.
[0040] In step 2) of the present invention, the Fe precursor solution is selected from one or more of iron (IID) nitrate nonahydrate, iron (I) acetylacetonate or iron (III) porphyrin.
[0041] In the preparation method provided by the present invention, step 3) is to subject the doping system obtained in step 2) to a hydrothermal reaction in a reactor to obtain Fe-doped ALPO crystals. Specifically:
[0042] In step 3) of the present invention, the temperature of the hydrothermal reaction is 130-200°C, and can be optionally 130-160°C or 160-200°C.
[0043] In step 3) of the present invention, the time of the hydrothermal reaction is 20 to 30 hours, and can be optionally 20 to 24 hours or 24 to 30 hours.
[0044] In step 3) of the present invention, the reaction kettle is an autoclave, for example, a stainless steel autoclave lined with polytetrafluoroethylene.
[0045] In a specific embodiment, the doped system was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160° C. for 24 hours to promote the growth of Fe-doped ALPO crystals.
[0046] In the preparation method provided by the present invention, step 4) is to further activate the Fe-doped ALPO crystals obtained in step 3) to obtain a CO2 adsorbent based on Fe-based aluminum phosphate. Specifically:
[0047] In step 4) of the present invention, the activation includes calcination and pyrolysis.
[0048] In step 4) of the present invention, the present invention optimizes the temperature and time parameters of the calcination activation method in detail. The calcination treatment is carried out in air, and the calcination temperature is 125-525°C; the calcination time is 1.5-3.5 hours to remove the structure directing agent and completely open the pores. Optionally, the calcination time can be, for example, 125-250°C, 250-400°C, 400-525°C, 250-450°C, 450-525°C, etc. The calcination time can be, for example, 1.5-2.5 hours, 2.5-3.5 hours, etc. During the calcination process, the temperature increases gradually from 125-525°C, and then the temperature range is gradually narrowed until the optimal calcination activation temperature is found, and the time increases gradually from 1h to 3.5, and then the calcination time range is gradually narrowed until the optimal calcination time is found. The experimental results show that the sample calcined at 450°C for 2.5h exhibits a higher CO2 adsorption capacity.
[0049] In step 4) of the present invention, the present invention optimizes the temperature and pressure parameters of the pyrolysis activation method in detail. The pyrolysis is carried out under a nitrogen atmosphere, the pyrolysis temperature is 200-475°C, and the pressure is 0.1-2.0 bar, further optimizing the pore structure. Optionally, the pyrolysis temperature can be, for example, 200-300°C, 300-400°C, 400-475°C, etc. The pressure can be, for example, 0.1-1.0 bar, 1-2.0 bar, etc. During the pyrolysis process, the temperature increases gradually from 200°C to 475°C, and then the temperature range is gradually narrowed until the optimal pyrolysis activation temperature is found, and the pressure increases gradually from 0.1 bar to 2.0 bar, and then the pyrolysis pressure range is gradually narrowed until the optimal pyrolysis pressure is found. The experimental results show that the sample at 210°C and 0.35 bar exhibits a higher CO2 adsorption capacity.
[0050] As a further solution of the present invention: the adsorbent exhibits excellent thermal stability and chemical stability as evaluated by improved thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Specifically: The present invention proposes to comprehensively evaluate the thermal stability and chemical stability of the adsorbent by adopting improved thermogravimetric analysis (TGA) conditions, that is, under the condition of an oxygen flow rate of 50 mL / min, the temperature is increased from room temperature to 950°C at a heating rate of 5°C / min. In addition, combined with differential scanning calorimetry (DSC), the heat flow changes of the adsorbent during the heating process are synchronously monitored to obtain more comprehensive thermal behavior and chemical stability data.
[0051] As a further solution of the present invention: the adsorption isotherm data of the adsorbent under different temperature and pressure conditions are calculated by the Clausius-Clapeyron equation to obtain more accurate adsorption heat data. Specifically: the present invention proposes to collect adsorption isotherm data at multiple different temperatures of 25°C, 30°C, 35°C, 40°C and 45°C, and calculate the isotherm heat using the Clausius-Clapeyron equation to obtain more accurate adsorption heat data. At the same time, the adsorption heat data at different temperatures are statistically analyzed to evaluate the thermodynamic properties of the adsorption process and the performance stability of the adsorbent.
[0052] As a further solution of the present invention: the adsorbent exhibits good regeneration performance and cycle stability in a simulation of an actual rapid pressure swing adsorption (PSA) process. Specifically: the present invention proposes to introduce multiple adsorption-desorption cycle tests under different pressure and temperature conditions in a simulation of an actual rapid pressure swing adsorption (PSA) process to evaluate the regeneration performance and cycle stability of the adsorbent under different working conditions. By quantitatively analyzing the changes in the adsorption capacity of the adsorbent after multiple adsorption-desorption cycles, its regeneration efficiency and feasibility of long-term application are evaluated.
[0053]
CO2 adsorbent based on Fe-based aluminophosphate
[0054] The present invention also provides a CO2 adsorbent based on Fe-based aluminum phosphate, which is prepared by the preparation method of the CO2 adsorbent based on Fe-based aluminum phosphate as described above in the present invention.
[0055] In the Fe-based aluminum phosphate CO2 adsorbent provided by the present invention, the CO2 adsorption capacity of the Fe-based aluminum phosphate CO2 adsorbent is ≥4.9mmol / g under the conditions of 3 to 5bar and 20 to 30°C. The CO2 adsorption capacity of the Fe-based aluminum phosphate CO2 adsorbent under the conditions of 3 to 5bar and 20 to 30°C can be selected as ≥5.0mmol / g, ≥5.1mmol / g, ≥5.2mmol / g, ≥5.3mmol / g, ≥5.4mmol / g, ≥5.5mmol / g, ≥5.6mmol / g, ≥5.7mmol / g, ≥5.8mmol / g, ≥5.9mmol / g, etc.
[0056] Further optionally, the CO2 adsorption capacity of the Fe-based aluminum phosphate-based CO2 adsorbent at 4-5 bar and 20-30°C is ≥5.0mmol / g, and can be ≥5.1mmol / g, ≥5.2mmol / g, ≥5.3mmol / g, ≥5.4mmol / g, ≥5.5mmol / g, ≥5.6mmol / g, ≥5.7mmol / g, ≥5.8mmol / g, ≥5.9mmol / g, etc.
[0057] Preferably, the CO2 adsorption capacity of the Fe-based aluminum phosphate-based CO2 adsorbent at 4 bar and 25°C is 5.2 to 5.9 mmol / g, for example, 5.8 to 5.9 mmol / g, 5.7 to 5.9 mmol / g, 5.6 to 5.9 mmol / g, 5.5 to 5.9 mmol / g, 5.4 to 5.9 mmol / g, or 5.3 to 5.9 mmol / g.
[0058] In the Fe-based aluminum phosphate CO2 adsorbent provided by the present invention, the Fe-based aluminum phosphate CO2 adsorbent has an adsorption heat of no more than 25 kJ / mol. This adsorption heat is very low in the industry and can effectively reduce the regeneration energy consumption of the adsorbent and accelerate the regeneration cycle of the adsorbent in rapid pressure swing adsorption (PSA).
[0059] In the Fe-based aluminum phosphate-based CO2 adsorbent provided by the present invention, the Fe-based aluminum phosphate-based CO2 adsorbent is spherical.
[0060] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0061] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0062] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0063] Example 1
[0064] A method for preparing an Fe-based aluminum phosphate (Fe-AlPO) high-efficiency CO2 adsorbent is carried out by a hydrothermal synthesis method. The method comprises the following steps:
[0065] S1. Pre-preparation: Aluminum isopropoxide is mixed with deionized water in a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0066] S2. Reaction: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0067] S3. Addition of structure-directing agent: triethylamine (TEA) as a structure-directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH value of 5 to 6.
[0068] S4: adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160° C. for 24 hours to promote the growth of ALPO crystals;
[0069] Among them, in the above steps, doping: by accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, the Fe metal precursor is doped into ALPO to optimize its lattice parameters and pore structure, thereby improving the adsorption performance of CO2;
[0070] In the above steps, the crystal morphology is controlled by precisely adjusting the molar ratio of water / Al2O3 to 100:1 to prepare spherical aggregates of Fe-AlPO (such as Figure 2 ) to optimize its void structure and specific surface area.
[0071] S5. Activation: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air, the temperature was set to 450°C, and the calcination time was 2.5h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere, the temperature was set to 210°C, and the pressure was set to 0.35bar to further optimize the pore structure.
[0072] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) showed the highest CO2 adsorption capacity, reaching 5.8 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 1.
[0073] Table 1 CO2 adsorption performance of 5Fe-AlPO in Example 1
[0074]
[0075] Example 2
[0076] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0077] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0078] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0079] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 4:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0080] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0081] Results: At 4 bar and 25 °C, spherical 4Fe-AlPO (Fe / Al2O3 molar ratio of 4:100) exhibited a high CO2 adsorption capacity of 5.5 mmol / g. In addition, the CO2 adsorption capacity of spherical 4Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 2.
[0082] Table 2 CO2 adsorption performance of 4Fe-AlPO in Example 2
[0083]
[0084] Example 3
[0085] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0086] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0087] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0088] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 6.5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0089] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0090] Results: At 4 bar and 25 °C, spherical 6.5Fe-AlPO (Fe / Al2O3 molar ratio of 6.5:100) exhibited a high CO2 adsorption capacity of 5.2 mmol / g. In addition, the CO2 adsorption capacity of spherical 6.5Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 3.
[0091] Table 3 CO2 adsorption performance of 6.5Fe-AlPO in Example 3
[0092]
[0093] Example 4
[0094] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 2 hours to ensure complete dissolution.
[0095] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0096] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0097] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0098] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0099] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.7 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 4.
[0100] Table 4 CO2 adsorption performance of 5Fe-AlPO in Example 4
[0101]
[0102] Example 5
[0103] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 4.5 hours to ensure complete dissolution.
[0104] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0105] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0106] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0107] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0108] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.9 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 5.
[0109] Table 5 CO2 adsorption performance of 5Fe-AlPO in Example 5
[0110]
[0111]
[0112] Example 6
[0113] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0114] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide:orthophosphoric acid=1:0.802) and stirring was continued for 0.75 hours to form a uniform reaction solution.
[0115] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0116] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0117] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0118] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.6 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 6.
[0119] Table 6 CO2 adsorption performance of 5Fe-AlPO in Example 6
[0120]
[0121] Example 7
[0122] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0123] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide:orthophosphoric acid=1:0.802) and stirring was continued for 1.75 hours to form a uniform reaction solution.
[0124] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0125] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0126] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0127] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.6 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 7.
[0128] Table 7 CO2 adsorption performance of 5Fe-AlPO in Example 7
[0129]
[0130] Example 8
[0131] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0132] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0133] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 18 hours to form a reaction gel with a pH of 5 to 6.
[0134] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0135] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0136] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.6 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 8.
[0137] Table 8 CO2 adsorption performance of 5Fe-AlPO in Example 8
[0138]
[0139] Example 9
[0140] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0141] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0142] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 30 hours to form a reaction gel with a pH of 5 to 6.
[0143] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0144] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0145] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.9 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 9.
[0146] Table 9 CO2 adsorption performance of 5Fe-AlPO in Example 9
[0147]
[0148] Example 10
[0149] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0150] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0151] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0152] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0153] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 200 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0154] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.8 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 10.
[0155] Table 10 CO2 adsorption performance of 5Fe-AlPO in Example 10
[0156]
[0157] Embodiment 11
[0158] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0159] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0160] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0161] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0162] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 475 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0163] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.4 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 11.
[0164] Table 11 CO2 adsorption performance of 5Fe-AlPO in Example 11
[0165]
[0166]
[0167] Example 12
[0168] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0169] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0170] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0171] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0172] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.10 bar to further optimize the pore structure.
[0173] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.5 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 12.
[0174] Table 12 CO2 adsorption performance of 5Fe-AlPO in Example 12
[0175]
[0176] Embodiment 13
[0177] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0178] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0179] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0180] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0181] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 450°C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210°C and a pressure of 2.00 bar to further optimize the pore structure.
[0182] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.7 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 13.
[0183] Table 13 CO2 adsorption performance of 5Fe-AlPO in Example 13
[0184]
[0185] Embodiment 14
[0186] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0187] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0188] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0189] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0190] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 125°C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210°C and a pressure of 0.35 bar to further optimize the pore structure.
[0191] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.3 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 14.
[0192] Table 14 CO2 adsorption performance of 5Fe-AlPO in Example 14
[0193]
[0194] Embodiment 15
[0195] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0196] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0197] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0198] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0199] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 525 °C for 2.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0200] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.9 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at several different temperatures and pressures was selected, and the results are shown in Table 15.
[0201] Table 15 CO2 adsorption performance of 5Fe-AlPO in Example 15
[0202]
[0203] Example 16
[0204] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0205] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0206] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0207] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0208] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 125°C for 1.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210°C and a pressure of 0.35 bar to further optimize the pore structure.
[0209] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.4 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 16.
[0210] Table 16 CO2 adsorption performance of 5Fe-AlPO in Example 16
[0211]
[0212] Embodiment 17
[0213] S1: Aluminum isopropoxide was mixed with deionized water at a weight ratio of 1:1.3 and kept under stirring for 3 hours to ensure complete dissolution.
[0214] S2: Orthophosphoric acid was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.802) and stirring was continued for 1 hour to form a uniform reaction solution.
[0215] S3: Triethylamine (TEA) as a structure directing agent was added dropwise at a molar ratio (aluminum isopropoxide: orthophosphoric acid = 1:0.74) and stirred for 24 hours to form a reaction gel with a pH of 5 to 6.
[0216] S4: Adding Fe precursor solution and additional water to the reaction gel to form a doping system, accurately adjusting the molar ratio of metal Fe / Al2O3 to 5:100, and accurately adjusting the molar ratio of additional water / Al2O3 to 100:1; the doping system is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and maintained at 160°C for 24 hours to promote the growth of ALPO crystals.
[0217] S5: The synthesized Fe-based aluminum phosphate high-efficiency adsorbent (Fe-AlPO) was activated by calcination and pyrolysis. The calcination treatment was carried out in air at a temperature of 125 °C for 3.5 h to remove the structure directing agent and fully open the pores. The pyrolysis treatment was carried out in a nitrogen atmosphere at a temperature of 210 °C and a pressure of 0.35 bar to further optimize the pore structure.
[0218] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) exhibited a high CO2 adsorption capacity of 5.5 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 17.
[0219] Table 17 CO2 adsorption performance of 5Fe-AlPO in Example 17
[0220]
[0221]
[0222] Comparative Example 1
[0223] The difference between this comparative example and Example 1 is that the molar ratio of water / Al2O3 in the synthetic mixture is adjusted to 400:1, and the 5Fe-AlPO crystals are controlled to present a columnar morphology (such as Figure 1 ), optimizing the pore characteristics of the adsorbent.
[0224] Results: Under the conditions of 4 bar and 25 °C, columnar 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) showed the highest CO2 adsorption capacity of 3.6 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 18.
[0225] Table 18 CO2 adsorption performance of 5Fe-AlPO in comparative example 1
[0226]
[0227] Combining Table 1 and Table 18, the adsorption capacity in Comparative Example 1 is reduced and the adsorption heat is significantly increased. However, Example 1 satisfies both the high CO2 adsorption capacity and the adsorption heat of less than 25 kJ / mol. The adsorption heat of less than 25 kJ / mol is very low in the industry and can effectively reduce the regeneration energy consumption of the adsorbent and accelerate the regeneration cycle of the adsorbent in rapid pressure swing adsorption (PSA). It can be significantly shown that the spherical structure in Example 1 is superior to the columnar structure in Comparative Example 1.
[0228] Comparative Example 2
[0229] The difference between this comparative example and Example 1 is that the molar ratio of metal Fe / Al2O3 in the synthetic mixture is adjusted to 3:100, the morphology of the ALPO crystal is controlled, and its lattice parameters and pore structure are optimized.
[0230] Results: At 4 bar and 25 °C, spherical 3Fe-AlPO (Fe / Al2O3 molar ratio of 3:100) showed the highest CO2 adsorption capacity of 3.5 mmol / g. In addition, the CO2 adsorption capacity of spherical 3Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 19.
[0231] Table 19 CO2 adsorption performance of 3Fe-AlPO in comparative example 3
[0232]
[0233] Combining Table 1 and Table 19, the adsorption capacity in Comparative Example 2 is reduced and the adsorption heat is significantly increased. Example 1 satisfies both the high CO2 adsorption capacity and the adsorption heat of less than 25 kJ / mol. The adsorption heat of less than 25 kJ / mol is very low in the industry and can effectively reduce the regeneration energy consumption of the adsorbent and accelerate the regeneration cycle of the adsorbent in rapid pressure swing adsorption (PSA). It can be significantly shown that the molar ratio of Fe / Al2O3 in Example 1 to 5:100 is better than the molar ratio of Fe / Al2O3 to 3:100 in Comparative Example 2.
[0234] Comparative Example 3
[0235] The difference between this comparative example and Example 1 is that the doped metal atom is magnesium.
[0236] Results: At 4 bar and 25 °C, spherical 5Mg-AlPO (Mg / Al2O3 molar ratio of 5:100) showed the highest CO2 adsorption capacity of 1.7 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Mg-AlPO at different temperatures and pressures was selected, and the results are shown in Table 20.
[0237] Table 20 CO2 adsorption performance of 5Mg-AlPO in comparative example 3
[0238]
[0239] Combining Table 1 and Table 20, the adsorption capacity in Comparative Example 3 is reduced and the adsorption heat is significantly increased. However, Example 1 satisfies both the high CO2 adsorption capacity and the adsorption heat of less than 25 kJ / mol. The adsorption heat of less than 25 kJ / mol is very low in the industry and can effectively reduce the regeneration energy consumption of the adsorbent and accelerate the regeneration cycle of the adsorbent in rapid pressure swing adsorption (PSA). It can be significantly shown that the doping metal Fe in Example 1 is better than the doping metal Mg in Comparative Example 3.
[0240] Comparative Example 4
[0241] The difference between this comparative example and Example 1 is that the doped metal atom is cobalt.
[0242] Results: At 4 bar and 25 °C, spherical 5Co-AlPO (Co / Al2O3 molar ratio of 5:100) showed the highest CO2 adsorption capacity of 2.7 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 21.
[0243] Table 21 CO2 adsorption performance of 5Co-AlPO in comparative example 4
[0244]
[0245] Combining Table 1 and Table 21, the adsorption capacity in Comparative Example 4 is reduced and the adsorption heat is significantly increased. However, Example 1 satisfies both the high CO2 adsorption capacity and the adsorption heat of less than 25 kJ / mol. The adsorption heat of less than 25 kJ / mol is very low in the industry and can effectively reduce the regeneration energy consumption of the adsorbent and accelerate the regeneration cycle of the adsorbent in rapid pressure swing adsorption (PSA). It can be significantly shown that the doping metal Fe in Example 1 is better than the doping metal Co in Comparative Example 4.
[0246] Comparative Example 5
[0247] The difference between this comparative example and Example 1 is that no metal atoms are doped.
[0248] Results: At 4 bar and 25 °C, spherical AlPO exhibited the highest CO2 adsorption capacity of 0.7 mmol / g. In addition, the CO2 adsorption capacity of AlPO at different temperatures and pressures was selected, and the results are shown in Table 22.
[0249] Table 22 CO2 adsorption performance of AlPO in Example 5
[0250]
[0251] Combining Table 1 and Table 22, the adsorption capacity in Comparative Example 5 is reduced and the adsorption heat is significantly increased. However, Example 1 satisfies both the high CO2 adsorption capacity and the adsorption heat of less than 25 kJ / mol. The adsorption heat of less than 25 kJ / mol is very low in the industry and can effectively reduce the regeneration energy consumption of the adsorbent and accelerate the regeneration cycle of the adsorbent in rapid pressure swing adsorption (PSA). It can be significantly shown that the doped metal Fe in Example 1 is better than the undoped metal in Comparative Example 5.
[0252] Comparative Example 6
[0253] The difference between this comparative example and Example 1 is that during the calcination activation process, the temperature is set to 600° C. and the calcination time is 4 hours.
[0254] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) showed the highest CO2 adsorption capacity of 3.7 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 23.
[0255] Table 23 CO2 adsorption performance of 5Fe-AlPO in comparative example 6
[0256]
[0257] Combining Table 1 and Table 23, the adsorption capacity in Comparative Example 6 is reduced and the adsorption heat is significantly increased. Example 1 not only meets the requirements of a high CO2 adsorption capacity, but also meets the requirements of an adsorption heat of less than 25 kJ / mol. The adsorption heat of less than 25 kJ / mol is very low in the industry and can effectively reduce the regeneration energy consumption of the adsorbent and accelerate the regeneration cycle of the adsorbent in rapid pressure swing adsorption (PSA). It can be significantly shown that the calcination temperature of 450°C in Example 1 is better than the calcination temperature of 600°C in Comparative Example 6.
[0258] Comparative Example 7
[0259] The difference between this comparative example and Example 1 is that during the pyrolysis activation process, the temperature was set to 550° C. and the pressure was set to 0.5 bar.
[0260] Results: At 4 bar and 25 °C, spherical 5Fe-AlPO (Fe / Al2O3 molar ratio of 5:100) showed the highest CO2 adsorption capacity of 3.7 mmol / g. In addition, the CO2 adsorption capacity of spherical 5Fe-AlPO at different temperatures and pressures was selected, and the results are shown in Table 24.
[0261] Table 24 CO2 adsorption performance of 5Fe-AlPO in comparative example 7
[0262]
[0263]
[0264] Combining Table 1 and Table 24, the adsorption capacity in Comparative Example 7 is reduced and the adsorption heat is significantly increased. Example 1 not only meets the requirements of high CO2 adsorption capacity, but also meets the requirements of adsorption heat below 25 kJ / mol. The adsorption heat below 25 kJ / mol is very low in the industry and can effectively reduce the regeneration energy consumption of the adsorbent and accelerate the regeneration cycle of the adsorbent in rapid pressure swing adsorption (PSA). It can be significantly shown that the pyrolysis temperature of 210°C in Example 1 is better than the pyrolysis temperature of 550°C in Comparative Example 7.
[0265] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate, characterized in that: The preparation method comprises the following steps: 1) mixing aluminum isopropoxide with water, dissolving under stirring, and then sequentially adding orthophosphoric acid and a structure directing agent to form a reaction gel; 2) adding Fe precursor solution and additional water to the reaction gel obtained in step 1) to form a doping system; wherein the aluminum isopropoxide is converted to Al2O3 based on the molar number of aluminum atoms, and the molar ratio of the additional water to Al2O3 is 100-250:1; 3) subjecting the doping system obtained in step 2) to a hydrothermal reaction in a reactor to obtain Fe-doped ALPO crystals; 4) Further activating the Fe-doped ALPO crystals obtained in step 3) to obtain a CO2 adsorbent based on Fe-based aluminum phosphate.
2. The method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate according to claim 1, characterized in that: Also includes any one or more of the following features: A1) in step 1), aluminum isopropoxide is mixed with water and stirred for 2 to 4.5 hours; A2) in step 1), the structure directing agent is one or more of triethylamine, tetraethylammonium hydroxide, and cyclohexylamine; A3) In step 1), the molar ratio of aluminum isopropoxide, orthophosphoric acid, and structure directing agent is 1:0.7-1.1:0.6-1.0; A4) In step 1), the orthophosphoric acid and structure directing agent are added dropwise; A5) in step 1), adding the orthophosphoric acid and stirring for 0.75 to 1.75 hours; A6) in step 1), adding the structure directing agent and stirring for 18 to 30 hours; A7) In step 1), the pH value of the reaction gel is 5 to 6.
3. The method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate according to claim 1, characterized in that: In step 2), the aluminum isopropoxide is converted to Al2O3 based on the molar number of aluminum atoms, the Fe precursor solution is converted to Fe based on the molar number of iron atoms, and the molar ratio of Fe to Al2O3 is 4:100 to 6.5:
100.
4. The method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate according to claim 1, characterized in that: In step 2), the Fe precursor solution is selected from one or more of iron (III) nitrate nonahydrate, iron (III) acetylacetonate or iron (III) porphyrin.
5. The method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate according to claim 1, characterized in that: Also includes any one or more of the following features: B1) In step 3), the temperature of the hydrothermal reaction is 130-200°C; B2) In step 3), the hydrothermal reaction time is 20 to 30 hours.
6. The method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate according to claim 1, characterized in that: In step 4), the activation includes calcination and pyrolysis.
7. The method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate according to claim 6, characterized in that: The calcination temperature is 125-525° C. and the calcination time is 1.5-3.5 hours.
8. The method for preparing a CO2 adsorbent based on Fe-based aluminum phosphate according to claim 6, characterized in that: The pyrolysis is carried out in a nitrogen atmosphere, the pyrolysis temperature is 200-475° C., and the pressure is 0.1-2.0 bar.
9. A CO2 adsorbent based on Fe-based aluminum phosphate, prepared by the preparation method of the CO2 adsorbent based on Fe-based aluminum phosphate as described in any one of claims 1 to 7.
10. The Fe-based aluminophosphate CO2 adsorbent according to claim 9, further comprising multiple of the following features: C1) the CO2 adsorbent based on Fe-based aluminum phosphate has a CO2 adsorption capacity of ≥4.9 mmol / g at 3-5 bar and 20-30° C.; C2) the Fe-based aluminophosphate-based CO2 adsorbent has an adsorption heat of no more than 25 kJ / mol; C3) The Fe-based aluminophosphate CO2 adsorbent is spherical.
Citation Information
Patent Citations
Preparation method of AlPO-18 molecular sieve membrane
CN103449475A
Zinc element doped AlPO-36 zeolite molecular sieve single crystal and preparation method thereof
CN118563404A
Visible light-responsive photocatalyst and its producing method
JP2008260011A
Metal silicoaluminophosphate molecular sieve with RHO framework structure, and method for preparing the same
US20150147269A1
Method for preparing light olefin through catalytic syngas with high selectivity by heteroatom-doped zeolite
US20210347711A1